2016
DOI: 10.1038/ncomms13753
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced nano-crystallization of silicate garnets from glass

Abstract: Transparent ceramics are important for scientific and industrial applications because of the superior optical and mechanical properties. It has been suggested that optical transparency and mechanical strength are substantially enhanced if transparent ceramics with nano-crystals are available. However, synthesis of the highly transparent nano-crystalline ceramics has been difficult using conventional sintering techniques at relatively low pressures. Here we show direct conversion from bulk glass starting materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 37 publications
3
51
0
1
Order By: Relevance
“…10 For the samples synthesized at higher temperatures (1400°C and 1600°C), the intercept method was used on more than 400 intercepts for each sample. The samples were prepared tõ 60 nm thick foils using the focused ion beam (FIB) technique (Helios NanoLab Dualbeam, FEI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10 For the samples synthesized at higher temperatures (1400°C and 1600°C), the intercept method was used on more than 400 intercepts for each sample. The samples were prepared tõ 60 nm thick foils using the focused ion beam (FIB) technique (Helios NanoLab Dualbeam, FEI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…10 In this way, transparent nanopolycrystalline kyanite (Al 2 SiO 5 ) ceramics with a small amount of corundum (a-alumina) were obtained under high pressure and temperature (high-PT). 10 In this way, transparent nanopolycrystalline kyanite (Al 2 SiO 5 ) ceramics with a small amount of corundum (a-alumina) were obtained under high pressure and temperature (high-PT).…”
Section: Introductionmentioning
confidence: 99%
“…Diverse sintering synthetic approaches have been employed for their elaboration, including vacuum sintering, hot isostatic pressing or spark plasma sintering with specific nanometer-scale raw powders 1 . There has been only very few reports of highly transparent nanocrystalline ceramic until the recent work on silicate garnets fabricated by direct conversion from bulk glass starting material in mutianvil high-pressure apparatus 16 . Nevertheless, all these processes require high-pressure and high-temperature sintering conditions, and it remains challenging to reach industrial production due to complex processes and reproducibility problems 1618 .…”
Section: Introductionmentioning
confidence: 99%
“…There has been only very few reports of highly transparent nanocrystalline ceramic until the recent work on silicate garnets fabricated by direct conversion from bulk glass starting material in mutianvil high-pressure apparatus 16 . Nevertheless, all these processes require high-pressure and high-temperature sintering conditions, and it remains challenging to reach industrial production due to complex processes and reproducibility problems 1618 . Ikesue et al 19 reported the possibility to prepare transparent YAG ceramics by pressureless slip casting and vacuum sintering at about 1800 °C but with large grain size (40–60 μm).…”
Section: Introductionmentioning
confidence: 99%
“…

interest in a wide range of applications, including missile guidance, infrared night vision, and laser and nuclear radiation detection. [6][7][8] Alternatively, more extreme synthesis techniques, including superhigh pressure, spark plasma sintering, and containerless processing may shift the grains toward submicrometer region; [9][10][11][12][13] however, the methods are inherently not scalable and also strictly limit the available sample size. Despite substantial progress in ceramic technology, it has been challenging to prepare this type of unique transparent nanoceramics with nanosized grains.

…”
mentioning
confidence: 99%